PROTECTION OF THE RIGHT OF THE CHILD TO BE HEARD IN DIVORCE PROCEEDINGS – HARMONIZATION OF CROATIAN LAW WITH EUROPEAN LEGAL STANDARDS - Lucić, Nataša (EU and comparative law issues and challenges series (ECLIC), 2018)
Contemporary developments in European procedural law reveal a growing interest in the protection and promotion of children’s (procedural) rights. The right of the child to be heard in proceedings resulting in decisions which directly or indirectly affect its rights and interests, is a procedural right of the child, granted by numerous European documents. One of such proceedings is certainly divorce proceedings involving children. This paper is aimed at demonstrating and analysing the ways in which the right of the child to be heard is protected in European law as well as at examining whether the protection of the right of the child to be heard in divorce proceedings in Croatian law is harmonized with the standards of European law in this legal area. Considering that the latest reform of Croatian family legislation (2015) has proposed some new solutions relating to the expression of child’s views in divorce proceedings, the author has conducted empirical research to examine the experiences of application of those solutions in legal practice.